Impact of Emulsifiers Addition on the Retrogradation of Rice Gels during Low-Temperature Storage - Zhe Yang; Xue Han; Huiying Wu; Lijuan Zhang; Lanwei Zhang; M. Javed Iqbal (Journal of Food Quality)
Rice and its products are widely consumed in Asian countries; however, starch retrogradation decreases the quality and shortens the shelf-life of rice foods particularly at low temperature. In this study sucrose ester (SE), glycerol monostearate (GMS), and sodium stearoyl lactylate (SSL) were added to rice flour and corresponding rice gels. Then, gelatinization properties, retrogradation characteristics, texture, and water content of these rice gels were investigated at 4°C and −20°C storage, respectively. The results demonstrated that the rice gels with 0.2% GMS had the lowest retrogradation index (ΔHr/ΔHg) (11.84%) and hardness (1359 g) at 4°C for a 10 d period, which was significantly lower in comparison to control and the other two emulsifiers (P<0.05). Adhesiveness and water content were increased compared to the other samples. Furthermore, the retrogradation of rice gels stored at 4°C was comparatively rapid compared to gels stored at −20°C. Gel samples stored at −20°C were still acceptable for more than 15 days. Thus it was revealed that GMS has the potential to retard starch retrogradation and produce high-quality rice products in preservation.